PENERAPAN PENDEKATAN PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS V SDN 012 PELANGKO KECAMATAN KELAYANG - Izhar Irian Nur; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve learning outcomes IPA class fifth students of SDN 012 Pelangko Kecamatan Kelayang with the application of learning approach contextual teaching and learning (CTL). that is the subject of this research is a fifth grade students enrolled. This type of research is a classroom action research (classroom actions research) which comprises two cycles (4 meetings). Based on the research and analysis of the data found that improving student learning outcomes using CTL learning approach is the basic score (63.75) with classical completeness 11 (39.29%) are in the poor category. At UH 1 (72.86) or after the application of classical completeness actions increased to 19 people (67.86%) with enough categories, UH 2 (84.29) classical completeness rose again to all students 28 people (100%) by category very good. Improving student learning outcomes are supported by the activity of teachers in the first cycle-one meetings to gain success 71.42% with good criterion. At the 2nd meeting increased to 82.14% with good criterion. In the second cycle to meeting all first gained success 89.28% with good criterion. At the 2nd meeting increased to 96.42% with very good qualifications. While the activities of students in the first cycle-one meetings to gain success 71.42% with good criterion. At the 2nd meeting of successes is 85.71% with both criteria. In the second cycle to meeting all first gained 89.28% success with the criteria very well. At the 2nd meeting increased to 92.85% with qualifications are also very good. Thus, it can be concluded that the application of CTL learning approach can improve learning outcomes fifth grade science students of SDN 012 Pelangko Kecamatan Kelayang Keywords: CTL learning approach, Learning Outcomes IPA